Kelayakan Instrumen Penilaian Higher Order Thinking Skills pada Materi Lingkungan - Kusuma Wardany; Sulis Anjarwati (ISEJ : Indonesian Science Education Journal, 2020)
Assessment is a measuring tool used in mastery of Higher Order Thinking Skills (HOTS) in environmental materials. Research on the development of this assessment instrument aims to determine the feasibility of assessing Higher Order Thinking Skills on environmental materials in SMA Surakarta. Research on the development of the Higher Order Thinking Skills (HOTS) assessment using the Research and Development (R&D) model refers to the modified Borg and Gall (1983). The sample to test the feasibility of the assessment includes 2 expert validators, namely material experts and evaluation instrument experts. The function of material experts and evaluation instrument experts is to validate the suitability of questions with indicators (construct validity) so as to ensure that the questions developed can measure students' Higher Order Thinking Skills. The results of the material expert validation show that the average score of all aspects of the material is 100% in the "Very Good" category. The results of the evaluation instrument expert validation show that the average score of all aspects of the material is 80.95% in the "Good" category, so that the Higher Order Thinking Skills (HOTS) assessment on environmental material is considered feasible to be tested in the limited test group or field tests on students.